Hyperhomocysteinemia enhances vascular inflammation and accelerates atherosclerosis in a murine model - Hofmann, Marion A. (American Society for Clinical Investigation, 2001)
Although hyperhomocysteinemia (HHcy) is a well-known risk factor for the development of cardiovascular disease, the underlying molecular mechanisms are not fully elucidated. Here we show that induction of HHcy in apoE-null mice by a diet enriched in methionine but depleted in folate and vitamins B6 and B12 increased atherosclerotic lesion area and complexity, and enhanced expression of receptor for advanced glycation end products (RAGE), VCAM-1, tissue factor, and MMP-9 in the vasculature. These homocysteine-mediated (HC-mediated) effects were significantly suppressed, in parallel with decreased levels of plasma HC, upon dietary supplementation with folate and vitamins B6/B12. These findings implicate HHcy in atherosclerotic plaque progression and stability, and they suggest that dietary enrichment in vitamins essential for the metabolism of HC may impart protective effects in the vasculature.